Shear behavior of the interface between asphalt concrete core and transition under seepage effect - Lifeng Wen; Jialuo Huang; Yu Yang (Scientific Reports)
Abstract Asphalt concrete core rockfill dam utilizes an asphalt concrete core as anti-seepage structure. Uneven deformation could produce at core wall-transition interface due to differences in material stiffness, potentially leading to crack formation in the core wall. Shear behavior of the interface is more complex under seepage effect. This study investigates the shear behavior of the asphalt concrete core-transition material interface under seepage effects. Shear tests were conducted across five seepage pressure, three shear rates, and five normal stress levels. A nuclear magnetic resonance system was employed to analyze internal pore distribution in the asphalt concrete core within shear-affected region. Additionally, high-pressure permeability tests were conducted to explore the effects of shear action on asphalt concrete core permeability. Findings revealed that the interface exhibited a shear hardening phenomenon, with normal displacement rising in response to increased seepage pressure, while the internal friction angle and cohesive strength diminished. The observed damage patterns primarily involved particle embedding, aggregate cracking, and surface cracking, with damage severity increasing with both normal stress and seepage pressure. Despite shear action leading to increased porosity, the asphalt concrete core remained compliant with porosity control standards.